Safety and Security in Transit Environments 2015
DOI: 10.1057/9781137457653_9
|View full text |Cite|
|
Sign up to set email alerts
|

Crowd Spatial Patterns at Bus Stops: Security Implications and Effects of Warning Messages

Abstract: As demonstrated throughout this book, the risk of certain types of crime can increase in congested spaces. Contact crimes, crimes which require the offender to make physical contact with the victim, are especially common in more crowded transport networks and can discourage many would-be passengers (Brand and Price, 2000). Pickpocketing makes up a substantial portion of this, accounting for around 50 per cent of all crime on London’s transport network (Transport for London, 2012). Other chapters in this volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…However, the surveillance theory by Jacobs (1961), Newman (1973), Skogan (1992), , , Ceccato (2020), Pain et al (2006), Clarke et al (1996), Loukaitou-Sideris et al (2009), La , , Ceccato and Bamzar (2016), and is challenged by the findings of Ramsay (1982), Soomeren (1996), Gentry (2015), Belanger (1999), Burrows (1980), Shellow et al (1975), Loukaitou-Sideris et al (2002, Bhattacharyya (2016), Sypion-Dutkowska and Leitner (2017), Dhillon and Bakaya (2014), Newton et al (2015), Solymosi et al (2015), Boessen and Hipp (2018), Newton (2004), , Crenshaw and John (1989), Talen (1996), and Roy and Bailey (2021), which revealed that the surveillance theory and environmental design including the layout of building plots, lightings, and police stations cannot establish a sense of community through strategies to unite people because the more the people on the streets, the more the opportunities for people to commit crimes. More trash, social chaos, social disorder, and social imbalance in the community also cause crime to occur.…”
Section: Open Accessmentioning
confidence: 99%
“…However, the surveillance theory by Jacobs (1961), Newman (1973), Skogan (1992), , , Ceccato (2020), Pain et al (2006), Clarke et al (1996), Loukaitou-Sideris et al (2009), La , , Ceccato and Bamzar (2016), and is challenged by the findings of Ramsay (1982), Soomeren (1996), Gentry (2015), Belanger (1999), Burrows (1980), Shellow et al (1975), Loukaitou-Sideris et al (2002, Bhattacharyya (2016), Sypion-Dutkowska and Leitner (2017), Dhillon and Bakaya (2014), Newton et al (2015), Solymosi et al (2015), Boessen and Hipp (2018), Newton (2004), , Crenshaw and John (1989), Talen (1996), and Roy and Bailey (2021), which revealed that the surveillance theory and environmental design including the layout of building plots, lightings, and police stations cannot establish a sense of community through strategies to unite people because the more the people on the streets, the more the opportunities for people to commit crimes. More trash, social chaos, social disorder, and social imbalance in the community also cause crime to occur.…”
Section: Open Accessmentioning
confidence: 99%
“…Pickpocketing in particular occurs at overcrowded spots at which offenders can take advantage of a high density of people who are close together (Loukaitou-Sideris et al 2001;. Research shows that these conditions are affected by the transit environment, for instance, Solymosi et al (2015) refer to a pedestrian motion analysis that found that in crowded environments safety problems occur due to bottlenecks, which are areas in which there is a significant capacity drop in pedestrian movement, such as a narrow doorway in a corridor, when jamming occurs when the incoming flow exceeds the capacity of the bottleneck. Other studies found a diminution of overall crime under crowded circumstances (e.g.…”
Section: Crowdednessmentioning
confidence: 99%